Carbon Particle Size from Galangal Rhizomes as the Sustainable Adsorbent: Synthesis and Mathematical Calculation Analysis in the Adsorption Isotherm Characteristics - Asep Bayu Dani Nandiyanto; Alifiyha Nayla Putri Akbar; Shilla Aulia Suhandi; Risti Ragadhita; Dwi Fitria Al Husaeni; Meli Fiandini; Abdulkareem Sh. Mahdi Al-Obaidi; Herry Saputra; Senny Luckyardi; Muhammad Aziz (Journal of Studies in Science and Engineering)
This study investigates the impact of carbon particle size derived from Galangal Rhizomes on adsorption isotherm characteristics, aiming to establish its effectiveness as an adsorbent. Galangal Rhizomes were selected due to their rich carbon compounds, including cellulose, hemicellulose, lignin, starch, pectin, and fiber, making them ideal for carbon-based adsorbents. The carbonization process involved subjecting Galangal Rhizomes to 250°C for 9 hours, then milling and sieving to obtain specific particle sizes (500, 1000, and 2000 µm). Characterization was done using digital microscopy and Fourier-transform infrared spectroscopy. Batch adsorption experiments were conducted using a curcumin solution as the model adsorbate, comparing results with ten standard isotherm models. Findings revealed that small carbon particles (500 µm) underwent monolayer adsorption, while large particles (1000 and 2000 µm) exhibited multilayer adsorption. The study concluded that Galangal Rhizomes-derived carbon particles are effective for colour waste cleanup, providing a natural, sustainable, and environmentally friendly solution aligned with sustainable development goals (SDGs).